The activation of GABAergic neurons in the hypothalamic tuberomammillary nucleus attenuates sevoflurane and propofol-induced anesthesia in mice - Jing Liu; Jing Liu; Jing Liu; Jing Liu; Xiao Liu; Xiao Liu; Xiao Liu; Wen-Yu Zhou; Wen-Yu Zhou; Wen-Yu Zhou; Jun Gan; Jun Gan; et al. (Frontiers Media S.A., 2023)
Background: The histaminergic neurons in the hypothalamic tuberomammillary nucleus (TMN) have been suggested to play a vital role in maintaining a rising state. But the neuronal types of the TMN are in debate and the role of GABAergic neurons remains unclear.Methods: In the present study, we examined the role of TMN GABAergic neurons in general anesthesia using chemogenetics and optogenetics strategies to regulate the activity of TMN GABAergic neurons.Results: The results indicated that either chemogenetic or optogenetic activation of TMN GABAergic neurons in mice decreased the effect of sevoflurane and propofol anesthesia. In contrast, inhibition of the TMN GABAergic neurons facilitates the sevoflurane anesthesia effect.Conclusion: Our results suggest that the activity of TMN GABAergic neurons produces an anti-anesthesia effect in loss of consciousness and analgesia.